2013
DOI: 10.1093/aob/mct219
|View full text |Cite
|
Sign up to set email alerts
|

Floral adaptation to local pollinator guilds in a terrestrial orchid

Abstract: Local pollinator adaptation through pollinator attraction was shown in the mountain populations, possibly due to adaptation to pollinating flies. The mountain plants were also observed to receive pollination from a greater diversity of pollinators than the lowland plants. The different floral phenotypes of the altitudinal regions are likely to be the consequence of adaptations to local pollinator guilds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 72 publications
(79 reference statements)
7
79
1
1
Order By: Relevance
“…Sun et al, 2014;van der Niet et al, 2014). Interestingly, we found no quantitative difference between the flower colours …”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Sun et al, 2014;van der Niet et al, 2014). Interestingly, we found no quantitative difference between the flower colours …”
Section: Discussioncontrasting
confidence: 58%
“…Such evidence can be derived from experiments where pollinators of one of the ecotypes are presented with an array of all the ecotypes to determine foraging preferences or pollination effectiveness (Ellis and Johnson, 2009;Newman et al, 2012). Arrays can be assembled under laboratory conditions and presented to captive insects (Galen, 1989;der Jager and Ellis, 2014) or arranged in the field by means of transplant experiments (Robertson and Wyatt, 1990;Newman et al, 2012;Sun et al, 2014) or by manipulating flowers within a population (Johnson and Steiner, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As with other floral traits, floral scents are known to vary within species, both within and among populations (Dötterl et al 2005;Chartier et al 2013;Mant et al 2005;Stökl et al 2009;Sun et al 2014), and this variability is strongly suggested to have a genetic basis (e.g., Andargie et al 2014;Friberg et al 2013;Zu et al 2016). However, little is known whether such genetic variability is the result of divergent selection or other scenarios (e.g., drift).…”
Section: Such Variations In Floralmentioning
confidence: 99%
“…The effectiveness of an olfactory signal depends on how well it matches the pollinator's perceptive abilities, and these olfactory traits are thus expected to diverge between plant populations experiencing different pollinator environments. Indeed, plants experiencing different pollinators among population were found to produce population-specific scents and likely be adapted to the locally available pollinator climate (Mant et al 2005;Stökl et al 2009;Sun et al 2014).…”
Section: Such Variations In Floralmentioning
confidence: 99%
See 1 more Smart Citation